Aerosol absorption measurements at the ALOMAR subarctic station - Montilla, Elena (2018)
The global study of atmospheric aerosol is one of the key factors in regards to climate change and those effects. Over the last 4 years a strong research work on aerosols properties characterization have been carried out into the Atmospheric Optics Group of the University of Valladolid (GOA-UVa) in Spain. We present the results about aerosol absorption coefficient measurements with two different techniques: the “integrating sphere photometer” and the particle soot absorption photometer (PSAP, Radiance Research). This data was acquired into the summer campaign 2008, made at north of Norway, like a result of the participation in-situ of GOA in the POLARCAT project, lead by the Norwegian Institute for Air Research, and included in the Fourth International Polar Year. Both methods are filter based and provide measurements that could be combined with optical column measurements for a better characterization of local aerosol. It contributes especially to the investigation of pollution events and to establishment the effects of the population over any local aerosol climatology. Based on this research background and the affordable and reliable instrumentation described in this work, the research can continue in Colombia in close collaborations with Spanish research groups.